ENHANCING LANGUAGE LEARNING THROUGH AUTHENTIC MATERIALS: STRATEGIES, BENEFITS, AND CHALLENGES IN THE CLASSROOM (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article emphasizes the importance of using authentic materials in language classrooms and the need for teachers to design activities that naturally integrate with these materials. It highlights that such activities should aim to enhance the materials without overcomplicating them with excessive analysis or manipulation. The primary goal is to create structured, purposeful tasks that encourage students to engage with real-world content in a natural way, following language acquisition principles. At the same time, these tasks should be manageable within the practical constraints of time and energy that exist in a typical classroom setting, ensuring a balanced and effective learning experience.